2015
DOI: 10.1007/s12035-015-9113-6
|View full text |Cite
|
Sign up to set email alerts
|

Absence of CCL2 and CCL3 Ameliorates Central Nervous System Grey Matter But Not White Matter Demyelination in the Presence of an Intact Blood–Brain Barrier

Abstract: A broad spectrum of diseases is characterized by myelin abnormalities, oligodendrocyte pathology, and concomitant glia activation, among multiple sclerosis (MS). Our knowledge regarding the factors triggering gliosis and demyelination is scanty. Chemokines are pivotal for microglia and astrocyte activation and orchestrate critical steps during the formation of central nervous system (CNS) demyelinating lesions. Redundant functions of chemokines complicate, however, the study of their functional relevance. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 88 publications
1
21
0
Order By: Relevance
“…Another possible explanation for the sex‐difference in the number of Iba1 immunoreactive cells at the lesion border could be a different rate of infiltration of peripheral immune cells, given that Iba1 is also expressed by macrophages and that the breakdown of the blood‐brain barrier facilitates a massive invasion of blood cells into the brain parenchyma. This phenomenon partially depends on the molecules expressed by the astrocytes forming the glial scar, such as the chemokines CCL2 and CCL3 (Janssen et al, ; Selenica et al, ). It has been described that CCL2 deficient expression in astrocytes leads to an impaired recruitment of peripheral immune cells and to a diminished reactivity of astrocytes and microglia, in a model of chronic EAE (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the sex‐difference in the number of Iba1 immunoreactive cells at the lesion border could be a different rate of infiltration of peripheral immune cells, given that Iba1 is also expressed by macrophages and that the breakdown of the blood‐brain barrier facilitates a massive invasion of blood cells into the brain parenchyma. This phenomenon partially depends on the molecules expressed by the astrocytes forming the glial scar, such as the chemokines CCL2 and CCL3 (Janssen et al, ; Selenica et al, ). It has been described that CCL2 deficient expression in astrocytes leads to an impaired recruitment of peripheral immune cells and to a diminished reactivity of astrocytes and microglia, in a model of chronic EAE (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…CCL2, also known as MCP-1, is a potent chemokine for the recruitment process of macrophages, monocytes, activated T cells and NK cells to the CNS [47]. MCP is an important member of the CC subfamily.…”
Section: Ccl2/ccr2mentioning
confidence: 99%
“…Among MCPs, MCP-1was the first one to be discovered and is the most characteristic CC subclass chemokine in humans [15]. CCL2 can be produced by cells such as endothelial cells, astrocytes, macrophages and microglia [47]. One study showed that the efflux of CCL2 may be mediated by the astrocyte ABC transporters (MRP-1 and P-glycoprotein), thereby promoting the migration of immune cells across the brain endothelial cells, involved in the process of neuroinflammation [57].…”
Section: Ccl2/ccr2mentioning
confidence: 99%
“…In considering previous work reporting early upregulation of chemokines in the cuprizone model Janssen et al, 2015), we decided to perform the analysis after 1 and 4 weeks of the cuprizone treatment. In considering previous work reporting early upregulation of chemokines in the cuprizone model Janssen et al, 2015), we decided to perform the analysis after 1 and 4 weeks of the cuprizone treatment.…”
Section: Cytokine and Chemokine Production In Cuprizone-treated Wt Anmentioning
confidence: 99%